Factors Affecting the Income of Oil Palm Farmers in Lambandia Village, Basalah Sub-district, South Konawe District - Muhammad Ikbal Patahillah; R. Marsuki Iswandi; Munirwan Zani (International Journal of Technology and Education Research, 2025)
This study aims to determine income and the factors that influence the income of oil palm farmers in Lambandia Village, Bassalah District, South Konawe Regency. The population in this study were all oil palm farmers in Lambandia Village, Basala District, South Konawe Regency, totaling 22 people, using the census technique, 22 respondents were obtained as the research sample. Data analysis used income analysis and multiple linear regression analysis where the data has been transformed into logarithmic form. The results showed that the income of oil palm farmers in Lambandia Village, Basala District, South Konawe Regency averaged IDR 42,985,442/year. Production costs (X3) have a negative effect on the income of oil palm farmers, while land area (X1) and price (X4) have a positive and significant influence on the income of oil palm farmers in Lambandia Village, Basala District, South Konawe Regency.